Cerebral embolic protection devices for stroke prevention in transcatheter aortic valve implantation: a meta-analysis. (14th October 2021) - Perez Camargo, D; Travieso Gonzalez, A; Carnero Alcazar, M; Cobiella Carnicer, J; Maroto Castellanos, L C; Taramasso, M
Abstract: Introduction: Stroke is a feared complication in patients undergoing transcatheter aortic valve implantation (TAVI), affecting up to 2.3% of patients in contemporary series. Cerebral embolic protection devices (CEPD) are designed to prevent embolization of debris during the procedure. Current evidence from randomized clinical trials (RCTs) and adjusted observational studies is controversial. Purpose: Study the influence of CEPD on stroke, mortality, silent ischemic lesions and neurocognitive function. Methods: A systematic search was conducted of the Cochrane Library, EMBASE, MEDLINE, Web of Science and conference abstracts in any language from database conception until March 2nd 2021 including RCTs or observational studies with propensity score (PS) adjustment comparing TAVI with or without the use of CEPD. Estimates for clinical outcomes (30-day stroke, death and composite) were combined using a random-effects meta-analysis using the Inverse of Variance method to determine the pooled odds ratio (OR) of CEPD compared with non-CEPD. For neurocognitive function assessment, results were pooled to obtain the relative risk (RR) using the Mantel-Haenzel method. Finally, continuous outcomes from the MRI cerebral evaluation were combined in a random-effects model with standardized mean difference (SMD) between EPD and non-EPD. Results: Twelve studies were eligible (n=165, 315), six RCTs and six observational studies with PS adjustment. Median age of the patients was 80.8 (IQR=80–81.84) in patients with CEPD and 80.92 (IQR=79.75–82.15) in non-CEPD. Previous stroke or transient ischemic attack was 588/25, 056 in CEPD and 673/25, 583 in non-CEPD. STS-PROM score was 5.6% (IQR=4.64–6.2) for CEPD and 6.41% (IQR=4.72–6.9) for non-CEPD. Pooled analysis detected no-significant differences between CEPD and non-CEPD (OR=0.74; 95% CI 0.52–1.06; P=0.101; I 2 =82.6%) for 30-day Stroke but a significant difference favoring CEPD (OR=0.75; 95% CI 0.68–0.82; P<0.000; I 2 =0%) for 30-day mortality (Figure 1). Regarding cerebral DW-MRI assessment and neurocognitive function evaluation, we observed no significant differences between groups (Figure 2) Conclusion: In the present metanalysis of six RCTs and six PS adjusted observational studies, the use of a CEPD during TAVI was associated with a lower risk in 30-day mortality. We found no statistical difference between TAVI with or without CEPD for 30-day stroke, total lesion volume per patient, number of ischemic lesions per patient and neurocognitive function assessments. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Spanish Society for Cardiovascular and Endovascular Surgery